Pengaruh Pandemi COVID-19 Terhadap Nilai Biologi Mahasiswa Semester Satu Fakultas Kedokteran Universitas Hang Tuah - GUNAWAN TANDEAN, PETER; ARUNDNI, PRIMA; LILIAWANTI, LILIAWANTI (Universitas Hang Tuah, 2025)
The COVID-19 pandemic has also had a significant impact on the education sector. The policy requires all activities carried out outside the home, including teaching and learning activities, to be stopped until the COVID-19 pandemic subsides. The change from face-to-face to online learning systems brings a number of problems that are challenges for the world of education. To determine the effect of the COVID-19 pandemic on the biology grades of first semester students of the UHT Faculty of Medicine in the 2017/2018, 2018/2019 and 2020/2021, 2021/2022 academic years. This study will use the cross-sectional group design method. This study used all first semester students of the Faculty of Medicine, Hang Tuah University, batch 2017/2018, 2018/2019 and 2020/2021, 2021/2022. RESULTS: In CBT, the results of the T test were obtained with insignificant results for the Biology scores of first semester students of the UHT Medical Faculty during the non-pandemic period of 2017/2018 with the pandemic period of 2020/2021 with p = 0.0085 (p ˂ 0.05). In SOOCA with the T test, the results were obtained with insignificant results for the Biology scores of first semester students of the UHT Medical Faculty during the non-pandemic period of 2017/2018 with the pandemic period of 2020/2021 with p = 0.078 (p ˂ 0.05). and Final Value with T-test obtained insignificant results of the Biology value of first semester FK UHT students during the non-pandemic period 2017/2018 with the pandemic period 2020/2021 with p = 0.054 (p ˂ 0.05). In CBT, the results of the T-test were obtained with significant results of the Biology value of first semester FK UHT students during the non-pandemic period 2017/2018 with the pandemic period 2021/2022 and 2021/2022 with p = 0.000 (p ˂ 0.05). ). In SOOCA and Final Value with T-test, significant results were obtained of the Biology value of first semester FK UHT students during the non-pandemic period 2018/2019 with the pandemic period 2021/2022 with p = 0.000 (p ˂ 0.05). In CBT, the results of the one-way ANOVA test were obtained with significant results for the Biology scores of first-semester FK UHT students during the 2018/2019 non-pandemic period with the 2020/2021 and 2021/2022 pandemic periods with p = 0.000 (p ˂ 0.05). In SOOCA and Final Scores with the T-test, significant results were obtained for the Biology scores of first-semester FK UHT students during the 2018/2019 non-pandemic period with the 2020/2021 and 2021/2022 pandemic periods with p = 0.000 (p ˂ 0.05). In the pre-pandemic academic year 2017/2018 and the pandemic academic year 2020/2021, there was a difference in the average CBT, SOOCA, and Final Scores for biology of first-semester FK UHT students. In the academic year before the pandemic 2017/2018 and the academic year during the pandemic 2021/2022, there was a difference in the average CBT, SOOCA, and Final Biology Scores of first-semester FK UHT students. In the academic year before the pandemic 2018/2019 and the academic years during the pandemic 2020/2021 and 2021/2022, there was a difference in the average CBT, SOOCA, and Final Biology Scores of first-semester FK UHT students. Keywords: